Injury patterns and demographics due to legal intervention seen in US emergency departments. (April 2021) - Loder, Randall T.; Leiser, Abraham
Abstract: Background: Injury and deaths inflicted by law enforcement are a topic of significant discussion in the US. The purpose of this study was to analyze injuries due to law enforcement activity that presented to emergency departments (ED) across the entire US and correlate the injury patterns with patient demographics. Methods: The National Electronic Injury Surveillance System (NEISS) All Injury Program (AIP) data was used for the years 2005 through 2015. Injuries due to legal/law enforcement activity were identified. Statistical analyses were performed with SUDAAN 11.0.01™. A p < 0.05 was considered statistically significant. Results: There were 939, 405 ED visits for non-fatal injuries due to law enforcement. The average age was 31.9 years; 84.6% were male. The mechanism of injury was being struck in 69.7%; firearm gunshot wounds accounted for only 1.2%. The most common location of injury was the head and neck (44.0%) followed by the upper extremity (20.2%). The vast majority of the patients (94.9%) were treated and released from the ED. The seven major diagnoses were contusion/abrasion (37.8%), strain/sprain (22.7%), laceration (12.9%), fracture (7.6%), puncture (8.2%), and foreign body (2.5%). The injuries with the highest percentage of hospital admissions were foreign bodies and fractures (11.4% and 11.3% respectively. Although the number of events occurring at schools or sporting venues was 2.0%, those seen at children's hospitals demonstrated a higher percentage at 15.6%. Conclusions: This data set provides another viewpoint of injuries inflicted by police. It can be used as baseline data for further studies, especially in the US recent sociopolitical environment calling for police reform and improvements in the education and training of police officers.